Numerical and experimental investigation of hydrogen-rich syngas production via biomass gasification - Aydin, Ebubekir Siddik; Yucel, Ozgun; Sadikoglu, Hasan (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In this work, the relation between hydrogen-rich syngas production and the gasification parameters such as equivalence ratio (ER), gasification temperature and biomass moisture content were studied. Stoichiometric equilibrium model that developed during this study was used to investigate the optimum hydrogen output generated from woody biomass in a fixed bed downdraft gasifier by considering the thermodynamic equilibrium limit. The mathematical model, based on thermodynamic equilibrium is necessary to understand complicated gasification process that will contribute to obtain maximum attainable hydrogen production. The effects of different oxidizing agents on the hydrogen concentration in the product gas as well as the effect of various air-biomass, oxygen-biomass and steam-biomass ratios were investigated. For validation, the results obtained from the mathematical model were compared with the experimental data obtained from the gasifier that uses air as gasification medium. The validated mathematical model was used to represent the gasifier that uses both oxygen and air-steam mixture as the gasification medium and the theoretical results were obtained for both cases. The theoretical results clearly show that the gasification process specially ones that use the air-steam mixture as the gasification medium can be used for hydrogen production. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Modeling; Hydrogen production; Gasification; Biomass; Oxidizing agent; DOWNDRAFT FIXED-BED; STEAM GASIFICATION; EQUILIBRIUM-MODEL; CO-GASIFICATION; GAS-PRODUCTION; WHEAT-STRAW; GASIFIER; WOOD; TAR; AIR; Chemistry; Electrochemistry; Energy & Fuels